Optimal wound closure techniques for thyroid and parathyroid surgery: A systematic review of cosmetic outcomes. (1st August 2019) - Lee, Kristina; Ward, Nicholas; Oremule, Babatunde; Mani, Navin
Abstract: Objectives: Cosmesis after surgical wound closure is an important outcome. This is relevant after thyroid and parathyroid surgery as anterior neck scars are visible and often of concern to patients. We aimed to investigate whether wound closure method influences cosmetic outcome in thyroid and parathyroid surgery, in particular using sutures, staples, steri‐strips and glue. Design: We performed a systematic review of MEDLINE, PubMed, EMBASE, CINAHL and Cochrane focusing on wound cosmesis following thyroid and parathyroid surgery. Searches were conducted using combinations of the search terms: thyroid/parathyroid surgery, wound/skin closure and suture, staples, clips, glue and steri‐strips, using appropriate MESH terms and Boolean operators. Main outcome measures: Primary outcome was wound cosmesis. Secondary measures were also extracted. Results: Initial search found 304 papers and after systematic review, a total of 10 studies compared different closure methods and cosmetic outcomes. There were nine randomised controlled trials and one cohort study, with a total of 712 patients. Three studies compared staples vs glue; three compared sutures vs clips; two compared suture vs steri‐strips and two studies for suture vs glue. In general, short‐term cosmesis was better with subcuticular sutures compared to glue or clips, long‐term cosmetic outcomes were not influenced by closure method. Conclusions: We found closure with subcuticular suture or steri‐strips produced superior short‐term cosmetic outcomes. Although long‐term cosmetic outcome is not influenced by closure method, given the superior cosmetic outcome and advantage of not needing removal, we recommend subcuticular sutures should be performed for wound closure in thyroid and parathyroid surgery.